2017
DOI: 10.1590/0004-282x20170018
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-alpha gene XbaI A > G polymorphism influences short-term cognitive decline in healthy oldest-old individuals

Abstract: Global aging is a challenging reality of this century. In 2010, there were 576 million people aged 65 years and over, worldwide. The expectation for 2050 is that this number will triple, reaching 1.5 billion people 1 . It is important to note that the highest population aging rates occur in developing countries. It is expected that between 2010 and 2050 the number of older people in developing countries will grow around 250%, while in developed countries the rate will be 71% 1 . Notably, the change in aging is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The specific ESR1 SNP detected as associated with cognitive impairment in our study is not in linkage disequilibrium with the SNPs reported in Yaffe et al (r2 ≤ 0.014) and are greater than 100 kB distant from these SNPs, therefore likely represent a different association signal. Genetic alterations in the estrogen metabolic pathway have been reported to be associated with risk of Alzheimer's Disease in a study of a southern Chinese population 52 and association of ESR1 with one-year cognitive decline in healthy oldest-old individuals has also been cited 53 . www.nature.com/scientificreports/ The RYR3 gene codes for the ryanodine receptor that functions to release calcium from intracellular storage for use in cellular signaling and biochemical processes.…”
Section: Discussionmentioning
confidence: 99%
“…The specific ESR1 SNP detected as associated with cognitive impairment in our study is not in linkage disequilibrium with the SNPs reported in Yaffe et al (r2 ≤ 0.014) and are greater than 100 kB distant from these SNPs, therefore likely represent a different association signal. Genetic alterations in the estrogen metabolic pathway have been reported to be associated with risk of Alzheimer's Disease in a study of a southern Chinese population 52 and association of ESR1 with one-year cognitive decline in healthy oldest-old individuals has also been cited 53 . www.nature.com/scientificreports/ The RYR3 gene codes for the ryanodine receptor that functions to release calcium from intracellular storage for use in cellular signaling and biochemical processes.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted to-date demonstrate that persons with genotype XbaI GG remain stable or show improvement with respect to cognitive functioning [ 48 ], while those with genotype XbaI AA are at an increased risk of the development of AD [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The challenging reality of this century is global aging. According to one study, about 576 million people having 65 years of age and above were present in 2010 (Chaves et al, 2017). By the year 2050, this number will become 1.5 billion (Lara, 2018).…”
Section: Introductionmentioning
confidence: 99%